Evaluation of a Multilocus Sequence Typing (MLST) scheme for Leishmania (Viannia) braziliensis and Leishmania (Viannia) panamensis in Colombia - Herrera, Giovanny (Parasit Vectors, 2017)
BACKGROUND: Leishmaniases are parasitic vector-borne diseases affecting more than 12 million people in 98 countries. In Colombia, leishmaniasis is widespread and the most common clinical manifestation is cutaneous, mainly caused by L. panamensis and L. braziliensis. Currently, the genetic diversity of these species in Colombia is unknown. To address this, we applied molecular techniques for their characterization, using multilocus sequence typing (MLST) to explore the genetic variability and phylodynamics of the disease. METHODS: Seven previously described genetic markers were selected highlighting the implementation of a mitochondrial marker. Markers were applied to 163 samples from isolates obtained between 1980 and 2001. RESULTS: The identification of the samples showed an excellent correlation with typing tests previously applied (MLEE, monoclonal antibodies). Isolates of L. braziliensis showed greater genetic diversity than L. panamensis, and a greater number of diploid sequence types (DSTs). In addition, the geographical distribution of DSTs for each species were obtained through georeferencing maps. CONCLUSIONS: To our knowldge, this study represents the first description of the genetic variability of L. panamensis in Colombia and South America, and is the first to propose a scheme of MLST for epidemiological surveillance of leishmaniasis in the country. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13071-017-2175-8) contains supplementary material, which is available to authorized users.